Enhanced CO selectivity and stability for electrocatalytic reduction of CO2 on electrodeposited nanostructured porous Ag electrode. (September 2016) - Wang, Hua; Han, Zhenzhen; Zhang, Libo; Cui, Chaonan; Zhu, Xinli; Liu, Xiao; Han, Jinyu; Ge, Qingfeng
Graphical abstract: Highlights: A porous Ag foam electrode with average pore size of 10–25 μm and porous wall composed of 40–100 nm Ag nanoparticles. The competing hydrogen evolution reaction remarkably slow down and the onset potential of CO2 reduction occurs at 0.15 V less than that on Ag foil electrode. High current density and CO faradaic efficiency of over 90% were stable over the course of several hours. Abstract: Nanostructured electrocatalysts for CO2 reduction have attracted much attention due to their unique properties compared to their bulk counterparts. Here we report the synthesis of porous Ag foams on a polished Ag substrate via electrodeposition using the hydrogen bubble dynamic template. The as-prepared porous Ag foams has an average pore size of 10–25 μm with the porous wall composed of 40–100 nm Ag nanoparticles. CV tests indicate that the competing hydrogen evolution reaction remarkably slow down on porous Ag electrode and the onset potential of CO2 reduction occurs at 0.15 V less than that on the Ag foil electrode. Moreover, the high current density and CO faradaic efficiency of over 90% were stable over the course of several hours, whereas Ag foil electrode exhibited the drop of CO faradaic efficiency from 74.4% to 58.6% under identical conditions. We found that the enhanced activity and stability are the result of a large electrochemical surface area (approximately 120 times larger) which can provide more active sites. The noteworthy difference between the two electrodes suggests that the nanostructured surface of porous Ag foams is likely to not only favor the formation of CO2 − intermediate but also suppress the competitive reaction of hydrogen evolution.